Determinan Employee Performance: Peran Mediasi Employee Engagement di Industri Teknologi di Indonesia - Bayudi Ramadani; Justine Tanuwijaya; Andreas Wahyu Gunawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
In the era of globalization and rapid technological advancements, the technology industry has become one of the most dynamic and competitive sectors. Employee performance in this industry plays a crucial role in determining the success and competitiveness of companies. Optimal employee performance not only contributes to the company's productivity but also drives innovation, operational efficiency, and customer satisfaction. This study aims to examine the factors influencing employee performance through the mediation of employee engagement in the Indonesian technology industry, specifically companies engaged in insurance and crowdfunding. The research employs a quantitative approach with survey methods, gathering data from 241 employees from two major technology companies in Indonesia. The variables studied include Perceived Organizational Support (POS), trust and respect, organizational commitment, and organizational culture. The results indicate that Perceived Organizational Support, trust and respect, organizational commitment, and organizational culture significantly influence employee engagement, which in turn positively impacts employee performance. Data obtained were analysed using SmartPLS application to test causal relationships among the research variables. The findings underscore the importance of fostering a supportive, respectful, and committed organizational environment to enhance employee engagement and performance. This research makes a significant contribution to human resource management literature by demonstrating that employee engagement plays a crucial mediating role in the relationship between organizational determinants and employee performance.